Diffuse Large B-Cell Lymphoma with Calf Muscle Localization - Bourdeanu, Laura; Menon, Rashmi; Somlo, George (Case Reports in Hematology, 2011)
Although diffuse large B-cell lymphoma (DLBCL) usually occurs in the lymph nodes, approximately 30–40% of the time it can have an extranodal site of involvement and it can arise in nearly every body site such as intestine, bone, breast, liver, skin, lung, and central nervous system. Muscle involvement of DLBCL is especially uncommon, comprising 0.5% of extranodal NHL. We report a case of a 72-year-old man with extranodal DLBCL of a unique manifestation in the calf muscle, involving predominantly the gastrocnemius muscle. The patient achieved complete response and remained free of local recurrence or metastasis following diagnosis.